Flow injection determination of nitrate in vegetables using a tubular potentiometric detector - Lima, José L. F. C. (2011)
A flow injection system with potentiometric detection for the determination of nitrate in vegetables was developed. For this purpose a tubular nitrate ion-selective electrode with the ion-exchanger system [(4,7-diphenylphenanthroline)nickel(IId) issolved in o-nitrophenyl octyl ether] immobilized in a PVC membrane and without inner reference solution was prepared. The flow injection manifold incorporating the tubular electrode was used for the determination of nitrate in vegetables (lettuce, parsley, and spinach), using a mixture of lead acetate, lead oxide, and sodium acetate as nitrate extractant, ionic strength adjustor, and interference suppressor solution. The quality of the results obtained by the proposed methodology was assessed by comparing them with those provided by a conventional potentiometric methodology and also through recovery tests (recoveries from 94 to 104% were found). A sampling rate of 120 samples per hour was achieved with a relative standard deviation lower than 2%.